Narratives of the therapeutic encounter psychoanalysis, talking therapies and creative practice - Bainbrigge, Susan; Scheurer, Maren (Cambridge Scholars Publishing, 2020)
This collection of essays explores the ways in which talking therapies have been depicted in twentieth century and contemporary narratives (life-writings, fiction and poetry) in French. This vibrant corpus of francophone literary engagements of therapy has so far been widely unexplored, but it offers rich insights into the connections between literature and psychoanalysis. As the number of autobiographical and fictional depictions of the therapeutic encounter is still on the rise, these creative outputs raise pressing questions: why do narratives of the therapeutic encounter continue to fascin.